Nosema or Vairimorpha: Genomic/proteomic support to a complex socio-economic issue rooted in taxonomic change - Bojko, Jamie; Becnel, James; Bessette, Edouard; Edwards, Sam; Gao, Jing; Huang, Wei-Fone; Katanić, Nataša; Khalaf, Amjad; Li, Tian; Snow, Jonathan W; Solter, Leellen F; Stratton, Cheyenne E; et al. (Journal of invertebrate pathology, 2025)
Microsporidia are disease-causing organisms that can infect invertebrate species. In apiculture, two microsporidians of importance are Vairimorpha (=Nosema) ceranae and Vairimorpha (=Nosema) apis. The taxonomy surrounding the genus assignment of these species has been heavily debated, due to molecular systematic and socio-economic reasons. We provide an update to this debate by developing a 508-gene concatenated protein phylogeny, and a 277-gene concatenated nucleotide phylogeny, to show that these parasites show strong phylogenetic positioning with the Vairimorpha genus and its type species Vairimorpha necatrix. Despite this assignment, we suggest that the terms 'nosema-disease', 'nosemosis' and 'nosematosis' should still be viable for use within apiculture, and be named after the family Nosematidae in which V. ceranae and V. apis sit, instead of the previous genus assignment: Nosema.
Keywords: Nosema; Animals; včely; Phylogeny; Genomics; Proteomics; Bee; Nosematidae; zvířata; proteomika; Taxonomy; fylogeneze; Apiculture; Microsporidia; Nosemosis; Bees; genomika